Preparação e caracterização de estruturas polimórficas da tolbutamida e nifedipina - Souza, Kellen Christina Dutra de (2005)
In this study the polymorphs of tolbutamide, an oral hypoglicemiant used on Diabetes Mellitus type II treatment, and of nifedipine, a drug used in the cardiovascular disorders treatment, were prepared. All crystalline forms were obtained by crystallization from different solvents. Tolbutamide was isolated only in crystalline forms and nifedipine in two crystalline forms and in the amorphous form prepared by melting and subsequent cooling. The polymorphs from each drug were characterized by powder x-ray diffraction (PDRX), infrared spectroscopy (IR), Raman spectroscopy (FT-RAMAN), scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The results proved that two different crystalline forms of tolbutamide were obtained and two crystalline form to nifedipine, one of them as a pseudo-polymorph. The characterization confirmed that melting and quickly cooling procedure prepared amorphous nifedipine. Differential scanning calorimetry technique generated curves whose data proved that the amorphous nifedipine is a very unstable form. Thermogravimetry confirmed a pseudo-polymorphs preparation of nifedipine. In spite of the modification observed on the profile of X-ray diffraction, because of the solvent present, was possible to prove that this solvated form have an crystalline structure. A methodology was proposed step by step to prepare and characterize polymorphs of a substance